OBJECTIFICATION OF THE ABILITY TO PROVIDE FOR PARAMETERS: CONSTRUCTION OF QUANTITATIVE INDICATORS IN INDONESIAN MARRIAGE LAW - Fanridhal Engo (ASIAN PUBLISHER, 2026)
This study aims to analyze the concept of